Surgical Treatment of Objective Patellar Instability: Long-Term Results - Berruto, Massimo; Uboldi, Francesco Mattia; Ferrua, Paolo; Vergottini, Giovanni; Manunta, Andrea (Joints, 2018)
Purpose To evaluate the long-term results of classical “à la carte” surgical treatment of objective patellar instability as proposed by Dejour in 1987.Methods A multicentric retrospective study was conducted evaluating patients that underwent surgical procedure with a 10-year minimum follow-up (mean 12.7; range, 10–15). Surgical procedures were medial transfer of the tibial tubercle transfer according to Elmslie and Trillat et al in 38 cases, plasty of the vastus medialis obliquus according to Insall in 15 cases, open lateral retinacular release in 13 cases, capsuloplasty in 3 cases, and trochleoplasty in 1 case. Different combinations of surgical procedures were adopted according to the pathological features. Subjective outcome was assessed with the visual analog scale (VAS), Kujala score, subjective International Knee Documentation Committee (IKDC) score, Tegner score, and Crosby and Insall scale. Radiographic exams were used to assess the patellar tilt by the Laurin's angle and patellofemoral osteoarthritis (OA) according to the Iwano radiological OA scale.Results Forty patients were evaluated. Subjectively, 60% of patients achieved a result judged good, 34% sufficient, and 6% poor. There were only two cases of recurrence of instability. Mean score results were Kujala score 73.4 ± 9.9 (range, 55–95), VAS 4.5 ± 1.2 (range, 1–6), IKDC 64.8 ± 7.9 (range, 51–88), and Tegner score 4. Only nine patients returned to sports activities). Ten patients developed a grade I patellofemoral OA, 8 patients a grade II, and 22 patients a grade III. Average patellar tilt was 10° ±  3.9°.Conclusion This retrospective study showed that the traditional surgical procedure was successful for the treatment of patellar instability, but it did not prevent symptomatic patellofemoral OA.Level of Evidence Level IV, retrospective case series.
Keywords: patellar instability; patellofemoral; Elmslie–Trillat; osteoarthritis; tibial tubercle transfer